2022
DOI: 10.1302/0301-620x.104b2.bjj-2021-0764.r2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of deep vein thrombosis using routine pre- and postoperative duplex Doppler ultrasound in patients with pelvic trauma

Abstract: Aims The aims of this study were to assess the pre- and postoperative incidence of deep vein thrombosis (DVT) using routine duplex Doppler ultrasound (DUS), to assess the incidence of pulmonary embolism (PE) using CT angiography, and to identify the factors that predict postoperative DVT in patients with a pelvic and/or acetabular fracture. Methods All patients treated surgically for a pelvic and/or acetabular fracture between October 2016 and January 2020 were enrolled into this prospective single-centre stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…3 Our results revealed that mechanical injuries and traffic accidents were the main acquired factors, especially in the victims aged 40 to 59 years. Numerous clinical studies have been reported that fractures of long bones of lower limbs and pelvis are the most common fractures that contribute to deep venous thrombosis, 12,13 which was consistent with our results that lower extremity long bones and pelvic fractures were the commonest fractures related to PTE. It is worth to note that other accompanied factors, such as postinjury surgical intervention and prolonged bed rest, would also facilitate the formation of thrombus in victims with fractures.…”
Section: Discussionsupporting
confidence: 93%
“…3 Our results revealed that mechanical injuries and traffic accidents were the main acquired factors, especially in the victims aged 40 to 59 years. Numerous clinical studies have been reported that fractures of long bones of lower limbs and pelvis are the most common fractures that contribute to deep venous thrombosis, 12,13 which was consistent with our results that lower extremity long bones and pelvic fractures were the commonest fractures related to PTE. It is worth to note that other accompanied factors, such as postinjury surgical intervention and prolonged bed rest, would also facilitate the formation of thrombus in victims with fractures.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is easily influenced by factors such as vascular variation, obesity, anatomical structure, and doctors' experience, which can lead to missed diagnoses. 12,13 In recent years, researchers have begun to explore the feasibility of a combination of imaging examination and serological indicators in the diagnosis of DVT and have achieved good results. In this study, patients with IDDVT were examined using a combination of the Doppler ultrasound and the thrombus molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler ultrasound is the most common examination method in diagnosing DVT clinically as it is non‐invasive, safe, low‐cost, has good repeatability, and is convenient for observing the development of the disease. However, it is easily influenced by factors such as vascular variation, obesity, anatomical structure, and doctors' experience, which can lead to missed diagnoses 12,13 . In recent years, researchers have begun to explore the feasibility of a combination of imaging examination and serological indicators in the diagnosis of DVT and have achieved good results.…”
Section: Discussionmentioning
confidence: 99%